A simple analytical model for bamboo-reinforced slopes using modified Bishop method - Chakrabortty, Pradipta; Srivastava, Lokesh Sharan; Kumar, Pintu (Frontiers in Built Environment, 2023)
Introduction: Embankments are constructed in many places for transportation purposes such as railways and roads. The stability of slopes in embankments has always been a concern, especially in cohesionless soils. There are many methods to increase the safety factor of cohesionless soil slopes using geogrids, geocells, concrete piles, and so on. The conventional material used to stabilize slopes has a huge impact on the environment. Nowadays, researchers are using natural fibers such as bamboo and coir fiber for stabilization purposes. Methods: In this paper, bamboo piles are used to stabilize slopes. The bamboo piles are inserted vertically on the slope face to increase the shear strength and stability against slope failure. A limit equilibrium method has been developed to estimate the stability of a slope improved by friction piles after modifying the Bishop method of slices. The stability of the slope is analyzed for both the reinforced conditions and the unreinforced conditions using the developed analytical formula. Results and Discussion: The analytical equations were developed by considering three modes of slope failure: shear failure of the bamboo piles along the failure surface, movement of the upper part of the soil, leaving the bamboo pile embedded in the base soil, and pulling out of the bamboo along with the upper part of the soil mass. Further validation of the results is carried out with the limit equilibrium method-based software SLOPE/W using a modified Bishop method. The factor of safety increased after reinforcing the slope with bamboo piles for all three modes.